Traits of Innovative Leadership - Brusila-Meltovaara, Kristiina; Lampropoulos, Georgios; Makkonen, Pekka; Siakas, Kerstin (Academic conferences international, 2025)
Innovations are essential in maintaining or obtaining a competitive advantage. Innovations emerge from the combination of new resources and creative efforts, providing a significant foundation for economic growth. By promoting a culture of innovation, an organization’s ability to innovate is strengthened. Innovative companies are better positioned to utilize the full potential of external knowledge and resources to enhance their innovation activities and, in turn, gain competitive advantages. The culture of an organization is directly affected by the leadership of an organization. Leadership can promote a culture valuing creativity and risk taking while also encouraging employees to seek innovative ideas. Innovative leadership is also characterized by the ability to inspire and motivate teams to embrace change. Innovative leadership involves setting a clear vision, fostering a culture of continuous learning, and encouraging collaboration across all levels of the organization. Organizations are faced with rapidly changing environments and smart technologies. Innovative leaders are adaptable to changing environments and new technologies, open to new ideas, and skilled at leveraging diverse perspectives to drive growth and improvement. Innovative leaders also place great emphasis on effective communication and collaboration. An online questionnaire was distributed to Master level students at two universities of applied sciences in Finland. The participants had several years of work experience as at least two years of relevant work experience after their first degree is required for them to be eligible to apply. The questionnaire was distributed to identify the traits of innovative leaders and the importance of organizational culture and values as elements of innovative leadership. The research aims to establish how various leadership factors, including understanding content technologies, communication with stakeholders, visionary thinking, and internal and external conditions, influence the effectiveness and innovation of leadership within an organization. The relationship between different aspects of leadership and their impact on organizational success and innovation are also examined in this study.
Keywords: innovation; enterprise; organization; innovative leadership traits; innovative leadership; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|